Dynamics of Shock Structure and Frontal Drag Force in a Supersonic Flow Past a Blunt Cone under the Action of Plasma Formation: A Recent Study - Znamenskaya, Irina; Chernikov , Vladimir; Azarova, Olga (Current Overview on Science and Technology Research Vol. 4, 2022)
The Chapter is devoted to the experimental and CFD investigation of a plasma formation impact on the supersonic flow over a body “blunt cone - cylinder”. Using high speed shadowgraphy, a series of schlieren pictures of bow shock wave - blast wave non-stationary interaction is obtained. The calculations that follow are based on the Euler equation system. The Mach number of freestream is 3.1. The plasmoid is represented by an instant energy explosion of a bounded gas volume with increased pressure. The dynamics of a shock wave structure formed by the interaction of a bow shock wave and a blast flow have been studied. The considerable amount of energy released to a supersonic flow (500J) allowed for the creation of a diagram showing the genesis and dynamics of the ensuing shock waves and contact discontinuities, as well as a significant reduction in drag force and stagnation pressure (near to 80%). Furthermore, the dynamics of a low density and high gas temperature zone, which becomes the primary factor reducing frontal body drag force, were investigated. The dynamics of the front surface drag forces have been investigated for various plasmoid energy values. Qualitative agreement of the numerical and experimental flow patterns was obtained.